Արցախի հայագիր դպրոցի պատմության զարգացման շրջանները - Հարությունյան, Գրիշա (ԱրՊՀ հրատ․)
В статье на основе анализа архивных данных и статей историко – педагогического содержания, опубликованных в периодической печати кратко представлены основные этапы развития армянской школы Арцаха. Автор по-новому освещает документальные данные касающиеся анализируемой проблемы. The article, based on the analysis of the historical data and articles with historical - pedagogical maintenance published in the periodical press, summarizes the main stages in the development of Artsakh Armenian school. The author newly highlights the documentary data concerning the problem being analyzed.
Keywords: Մանկավարժություն; Արցախ